Propofol induces the apoptosis of neural stem cells via microRNA-9-5p / chemokine CXC receptor 4 signaling pathway. Issue 1 (1st January 2022) - Zhang, Weixin; Liu, Qi; Zhu, He; Ma, Chao; Luo, Qin; Ji, Meilin; Liu, Li
ABSTRACT: Recent studies suggested that propofol, one of the most widely used anesthetics, may cause neurotoxicity in the developing brain, leading to cognitive deficits in adults. However, the underlying mechanisms remain unclear. In this study, we aimed to evaluate the mechanisms of propofol neurotoxicity in the neural stem cells (NSCs). The mRNA and protein expression levels of microRNA-9-5p (miR-9-5p) and chemokine CXC receptor 4 (CXCR4) were determined by quantitative reverse transcription-polymerase chain reaction and Western blotting analyses. Cell viability and apoptosis were evaluated using the cell counting kit-8 and Hoechst staining kits. The levels of apoptosis-related proteins B-cell lymphoma 2 (Bcl-2), Bcl-2-associated X protein, and caspase-3 were detected by Western blotting analysis. These results confirmed that propofol activated cell apoptosis in a dose-dependent manner. A significant increase in the miR-9-5p and CXCR4 expression was observed in the propofol-treated cells. The overexpression of miR-9-5p induced apoptosis in NSCs, accompanied by elevated apoptosis-related protein activity. Furthermore, mitigated CXCR4 expression reduced propofol-induced cell apoptosis. We conclude that propofol induces cell death in NSCs, and overexpression of miR-9-5p/CXCR4 contributes to propofol-induced cell apoptosis, which might be a target for developing novel strategies to treat propofol neurotoxicity.